2018
DOI: 10.3389/fmicb.2018.00609
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori the Latent Human Pathogen or an Ancestral Commensal Organism

Abstract: We dedicated this review to discuss Helicobacter pylori as one of the latest identified bacterial pathogens in humans and whether its role is mainly as a pathogen or a commensal. Diseases associated with this bacterium were highly prevalent during the 19th century and gradually have declined. Most diseases associated with H. pylori occurred in individuals older than 40 years of age. However, acquisition of H. pylori occurs mainly in young children inside the family setting. Prevalence and incidence of H. pylor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
0
18
0
2
Order By: Relevance
“…Main outcome of this review was that the vast majority of investigated papers reported a positive association between gastrointestinal microbiota and deterioration of AD. The most common reported microorganism was Hp, one of the identified bacterial pathogens in humans which its role is principally as a pathogen or a commensal [25]. Interestingly, a wide variety of different proposals for the pathogenesis have been reported by the authors of the reviewed articles, such as chronic inflammation, immunological mechanisms, apoptosis, disruption of BBB, intestinal dysbiosis and MetS-related atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…Main outcome of this review was that the vast majority of investigated papers reported a positive association between gastrointestinal microbiota and deterioration of AD. The most common reported microorganism was Hp, one of the identified bacterial pathogens in humans which its role is principally as a pathogen or a commensal [25]. Interestingly, a wide variety of different proposals for the pathogenesis have been reported by the authors of the reviewed articles, such as chronic inflammation, immunological mechanisms, apoptosis, disruption of BBB, intestinal dysbiosis and MetS-related atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that H. pylori may confer benefits to humans [75]. There is a growing body of work suggesting that H. pylori may behave like a commensal or a symbiont, depending upon the circumstances [7678]. The data on the potential importance of H. pylori to human health are discussed in the review article by Cover T. and Blaser M. [79].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while Marino et al (2019) associates gastric ulceration with Helicobacter pylori infections using a 1994 citation concerned with humans (Nomura et al, 1994), this assertion ignores research over the last quarter century that indicates that Helicobacter spp. can be a commensal organism in humans (Li & Perez-Perez, 2018) and other species (Terio et al, 2005;Yasuda et al, 2015) and that both captive and wild healthy cetaceans harbor Helicobacter spp. (Goldman et al, 2011).…”
Section: Are Killer Whales' Physical Needs Met Under Human Care?mentioning
confidence: 99%